Magnetic field impact on electrical properties of ZnSe-GaAs solid solutions - Brodovoy, А.V.; Veremenko, A.M.; Skryshevsky, V.A.; Vlasyuk, А.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
The influence of constant magnetic field on thermostimutated current, photoconductivity, and magnetic susceptibility of ZnSe-GaAs solid solutions were studied. It was shown that exposition in constant magnetic field results in the concentration decrease of electrically active deep traps. It leads to the change of mechanical and magnetic properties of ZnSe-GaAs solid solutions. Proposed was the healing mechanism based on inhomogeneous distribution of the magnetic susceptibility in crystal bulk and, therefore, the appearance of randomly distributed external magnetic fields. Interaction between magnetic moments results in appearance of “driving forces” promoting defect migration and their annihilation.